Sovremennye tekhnologii optimizatsii trenirovochnogo protsessa v sporte vysshikh dostizhenii (analiticheskii obzor noveishikh tekhnologii sportivnoi podgotovki) - Pankov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The modern system of an athlete training develops and improves all time. Among the factors optimizing an athlete training, the basic place is occupied by various means, both the methods of restoration and increase of sports preparedness. The optimum combination of the processes of the exhaustion and the restoration is the physiological basis of the constant and long-term adaptation of a human to physical and sports loadings. Therefore the application of the various means of restoration both the methods after training and competitive loadings are considered as the integral components of an athlete training. The operative restoration of the functional condition of an athlete should be carried out during everyone training occupation in view of the rules of the development and the indemnification of exhaustion in that occupation. The current restoration is directed on the maintenance of an optimum functional condition of an athlete in or after the process of loading on separate occupations with the purposes of training for the next work. The pedagogical, hygienic, medical-biological and psychological means in the modern system of restoration of an athlete are allocated conditionally.